2020
DOI: 10.1177/0734242x20946369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anisotropy in correlation structure on reliability-based slope stability analysis of a landfill

Abstract: In this study, a reliability-based analysis of slope stability in a landfill considering the spatial variability of shear strength (c and φ) and unit weight ( γ) of municipal solid waste was performed using the random finite difference method. The effect of the anisotropic correlation (AC) structure of random variables including c, φ, and γ on mean and coefficient of variation (CoV) of safety factor values was investigated using Monte Carlo simulation. Also, probability of failure was determined through probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…where X m is the mean value of the property and COV X is the coefficient of variation in the property. In structural reliability analyses, variables with a larger coefficient of variation exert a greater impact on the outcomes, whereas variables with a smaller coefficient of variation have a lesser impact [2,29]. Consistent with this principle, in the reliability analyses conducted within this study, both the friction angle and cohesion are treated as random variables, and the MSW unit weight is considered a constant.…”
Section: Mechanical Properties Of Mswmentioning
confidence: 90%
See 3 more Smart Citations
“…where X m is the mean value of the property and COV X is the coefficient of variation in the property. In structural reliability analyses, variables with a larger coefficient of variation exert a greater impact on the outcomes, whereas variables with a smaller coefficient of variation have a lesser impact [2,29]. Consistent with this principle, in the reliability analyses conducted within this study, both the friction angle and cohesion are treated as random variables, and the MSW unit weight is considered a constant.…”
Section: Mechanical Properties Of Mswmentioning
confidence: 90%
“…Therefore, various potential operational issues, such as high leachate levels, gas build-ups, and inadequate shear strength at the liner-MSW interface, have not been considered in these analyses. Analyses on simplified models, which include similar assumptions, are also introduced by other authors in studies that explore similar topics [2,12,22]. The model of the MSW landfill slope used in this study is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations